ANALISIS STUDI KELAYAKAN BISNIS UMKM RANINSHA KITCHEN DI BENGKALIS DITINJAU DARI ASPEK ASPEK PASAR, TEKNOLOGI, MENEJEMEN, SDM DAN SOSIAL EKONOMI - Amiratul Afifah; Ferlisa Sukmalika; Nurul Syuhada; Puji Afriyeni (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Feasibility study of a home-based culinary business called Raninsha Kitchen which focuses on the production and sale of snacks such as brownies, soft cookies, Belgian cookies, burnt cheesecake, and milk fruit pudding. The purpose of this study is to assess the feasibility of the business from various aspects, including market and marketing, engineering and technology, management, human resources, and economic and social impacts. The results of the analysis show that this business has broad market potential with an effective digital marketing strategy, supported by efficient home production even though it still uses simple equipment. Business management is carried out independently by the owner with the help of limited but competent workers. In addition, this business also has a positive impact on the surrounding community, both in terms of economy and social. Based on the results of the study from all aspects including market potential, engineering and technology aspects, management aspects, human resource aspects, and social and economic impacts, it can be concluded that the Raninsha Kitchen business has promising prospects. This business is considered feasible to run because it is able to provide comprehensive business feasibility indicators, and has great opportunities to be developed into a larger scale business in the future, both in terms of increasing production capacity, expanding the market, and professionalizing management.